2003
DOI: 10.1002/ajmg.a.20564
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐scan for loci involved in cleft lip with or without cleft palate in consanguineous families from Turkey

Abstract: Cleft lip with or without cleft palate (CL/P) is a common congenital anomaly, with birth prevalence ranging from 1/500 to 1/1,000. A number of genetic loci have shown positive linkage or association results in European Caucasian populations. The purpose of the current study was to assess whether any of those loci have positive results in Turkish Caucasian CL/P families, and to perform a 10 cM genome scan to identify other regions potentially containing cleft susceptibility loci. Eighteen affected individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 42 publications
5
32
0
4
Order By: Relevance
“…Recently, mutations in MSX1 have been identified in 2% of patients with nonsyndromic orofacial clefting [22,23•]. These data support previous associations of MSX1 with orofacial clefting [9, [24][25][26][27][28].…”
Section: P16 -Msx1supporting
confidence: 79%
See 1 more Smart Citation
“…Recently, mutations in MSX1 have been identified in 2% of patients with nonsyndromic orofacial clefting [22,23•]. These data support previous associations of MSX1 with orofacial clefting [9, [24][25][26][27][28].…”
Section: P16 -Msx1supporting
confidence: 79%
“…The first CL/P scan was performed on 92 British sibpairs and identified a total of nine regions with suggestive results [49]. This has been followed by five additional scans of varying size (Table 2) [20,24,[49][50][51][52][53][54]. In general, the results have been modest with the exception of a log odds ratio (LOD) score of 3.0 at 17p13.1 in a scan of two large Syrian families [50].…”
Section: Genome Scans Identify Novel Locimentioning
confidence: 99%
“…This region was first identified by Prescott et al in a genome scan of Caucasian NSCLP sib pairs, and subsequently in four other genome scans of different NSCLP populations (19,21,25,26,28). Analysis of STR D16S3037 in our dataset provided evidence for an association with NSCLP (P = 0.00063).…”
Section: Discussionsupporting
confidence: 60%
“…Egfr, Bmp4, Bmpr1 and Folbp1) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Eight genome scans have identified regions that may potentially harbor NSCLP susceptibility genes (19)(20)(21)(22)(23)(24)(25). In 2000, Prescott et al (26) identified nine chromosomal regions that are associated with orofacial clefting in their Caucasian NSCLP sib-pair population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation